2013
DOI: 10.1002/cbic.201200689
|View full text |Cite
|
Sign up to set email alerts
|

Beetles Do It Differently: Two Stereodivergent Cyclisation Modes in Iridoid‐Producing Leaf‐Beetle Larvae

Abstract: Larvae of the Chrysomelina species Phaedon cochleariae, Hydrothassa marginella, Phratora vulgatissima, Gastrophysa viridula, Gastrophysa atrocyanea, Gastrophysa cyanea and Gastrophysa polygoni produce the iridoid chrysomelidial (1) to defend themselves against predators. Feeding experiments with a deuterated precursor ([(2)H(5)]8-hydroxygeraniol 9) and in vitro isotope exchange experiments with defensive secretion in (2)H(2)O revealed differences in the cyclisation of the ultimate precursor 8-oxogeranial (8) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…After translocation of 8-hydroxygeraniol-O-β-d-glucoside into the defensive glands, its final transformation into iridoids occurs in the secretions. This transformation involves the hydrolysis of the glucoside and oxidation of the two primary hydroxy groups to produce the dialdehyde 8-oxogeranial, which is followed by a cyclization [52,54,39]. In general, hydrolysis of glycosides occurs in the metabolism of all organisms.…”
Section: Iridoid De Novo Synthesis: Late Stepsmentioning
confidence: 99%
See 3 more Smart Citations
“…After translocation of 8-hydroxygeraniol-O-β-d-glucoside into the defensive glands, its final transformation into iridoids occurs in the secretions. This transformation involves the hydrolysis of the glucoside and oxidation of the two primary hydroxy groups to produce the dialdehyde 8-oxogeranial, which is followed by a cyclization [52,54,39]. In general, hydrolysis of glycosides occurs in the metabolism of all organisms.…”
Section: Iridoid De Novo Synthesis: Late Stepsmentioning
confidence: 99%
“…Interestingly, with the same precursor, isotopic tracing studies have shown that there are two mechanistically different cyclization modes in different leaf beetle groups [39]. When deuterium atom labeled [ 2 H 5 ]Ger-8-OH was used for the feeding experiments, the precursor lost a single deuterium atom from C(4) in P. cochleariae, Hydrothassa marginella, and Phratora vulgatissima.…”
Section: Iridoid De Novo Synthesis: Late Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iridoidalkaloide sind bicyclische Monoterpene, die in Pflanzen und Insekten vorkommen und zur Verteidigung gegen Räuber dienen. Für die Cyclisierung von 8‐Oxogeranial ( 136 ) zu Iridodial ( 137 ), eine wichtige Zwischenverbindung in der Biosynthese der Iridoide, in Chrysomelina ‐Arten wurde eine Rauhut‐Currier‐Reaktion vorgeschlagen (Abbildung a) . Allerdings könnte die Biosynthese von Iridoiden in Käfern ganz anders ablaufen als in Pflanzen.…”
Section: Nukleophile Additionen An C‐c‐ Und C‐heteroatom‐mehrfachbinunclassified